Analysis Of Prabumulih University Student Satisfaction with the Capcut Application Using The End User Computing Satisfaction (EUCS) Method - Reisya Kurnia; Nur Aini H; Suhartini (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Technology is now increasingly developing so that it can make human work easier more quickly and support creativity through various applications. One application that supports creativity is the Capcut application. This research uses the End User Computing Satisfaction (EUCS) method. This research aims to determine the satisfaction of Prabumulih University students in using the Capcut application based on the variables content, accuracy, format, ease of use, timeliness and satisfaction. The research method used is quantitative descriptive. The data collection methods used were interviews, questionnaires and literature studies. The results of this research are that for each variable, students feel very satisfied in using the Capcut application, but for several variables such as accuracy and timeliness, they have been further improved to make it more satisfying to use the Capcut application.